Molecular Genetic And Immunological Diagnostic Markers Of Atopic Dermatitis - R. Razikova, Gulmira (Journal of Neonatal Surgery, 2025)
160 patients with various forms of atopic dermatitis aged 3 to 62 years who were under observation at the Republican Specialized Center for Dermatovenerology and Cosmetology were examined.The aim of the study was to identify early the molecular genetic and immunological mechanisms of atopic dermatitis development and to improve the diagnosis. Based on a clinical, immunological and molecular genetic examination of patients with atopic dermatitis, the domestic "Hepaprot-Neo" 0.45 included T330G of the IL-2 gene and 2258G>A of toll-like receptor genes of the TLR2 gene for complex treatment, taking into account allelic variants, based on the fact that an individualized pathogenetic treatment technique has been developed, which is characterized by the appointment of a drug that stabilizes the hepatoprotective membrane and enhances immunity.